2018
DOI: 10.1002/aoc.4543
|View full text |Cite
|
Sign up to set email alerts
|

Probing the adsorption behavior of oxazole and isoxazole heterocyclic compounds onto B12N12 nanocluster surface in gas and aqueous mediums through DFT calculations

Abstract: The adsorption of oxazole and isoxazole molecules over the pristine B 12 N 12 nanocluster is investigated in terms of its geometric, the adsorption energies and the electronic properties using density functional theory calculations.The results indicate that the pristine cluster effectively chemisorbs with the oxazole and isoxazole molecules through their nitrogen atoms; whereas the interaction through the oxygen atoms is not considerable. The HOMO-LUMO gap of the cluster decrease by the adsorption of heterocyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…To investigate the effect of environment on the D–A functionalized B 12 N 12 nanocluster, the role of solvent in the NLO properties of the molecules is also considered here. Hamooleh et al showed that aqueous solvent influences the adsorption properties of oxazole and isoxazole molecules over the surface of the B 12 N 12 nanocluster . They revealed that in aqueous solvent the thermodynamic stability increases for heterocyclic/B 12 N 12 complexes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the effect of environment on the D–A functionalized B 12 N 12 nanocluster, the role of solvent in the NLO properties of the molecules is also considered here. Hamooleh et al showed that aqueous solvent influences the adsorption properties of oxazole and isoxazole molecules over the surface of the B 12 N 12 nanocluster . They revealed that in aqueous solvent the thermodynamic stability increases for heterocyclic/B 12 N 12 complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Hamooleh et al showed that aqueous solvent influences the adsorption properties of oxazole and isoxazole molecules over the surface of the B 12 N 12 nanocluster. 45 They revealed that in aqueous solvent the thermodynamic stability increases for heterocyclic/B 12 N 12 complexes. In this work we also calculate the first hyperpolarizability of the studied complex in water (ε = 78.4) represented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…To make clear solvent effect on the interaction between GO and flavonoids, polarized continuum model (PCM) [ 25,26 ] was adopted in the calculation. All the geometry optimizations and the corresponding vibrational frequencies in solvents were performed with M06‐2X/6‐31G(d) based on the stable structures obtained in the gas phase.…”
Section: Methodsmentioning
confidence: 99%
“…[23] NBO analysis was adopted to investigate the charge transfer between GO and flavonoids, which is calculated from the charge concentration of flavonoids after and before adsorption. [24] To make clear solvent effect on the interaction between GO and flavonoids, polarized continuum model (PCM) [25,26] was adopted in the calculation. All the geometry optimizations and the corresponding vibrational frequencies in solvents were performed with M06-2X/6-31G (d) based on the stable structures obtained in the gas phase.…”
Section: Methodsmentioning
confidence: 99%
“…The highly parameterized M06-2X functional [24][25][26][27][28] was also employed to describe the coupling of the following coupling reaction of the generated α-acyloxy enol ester and dihydroisoquinoline without transition metals, and was compared with the M06-L results. Both the M06-L [29][30][31] and M06-2X [32,33] functionals can obtain reliable relative energies in describing noncovalent interactions. Moreover, M06-L can provide accurate information for reaction systems containing transition metals, and M06-2X has good performance in describing the main-group thermochemistry.…”
mentioning
confidence: 99%